2011
DOI: 10.1002/uog.7767
|View full text |Cite
|
Sign up to set email alerts
|

Fetal umbilical artery Doppler to predict compromise of fetal/neonatal wellbeing in a high‐risk population: systematic review and bivariate meta‐analysis

Abstract: K E Y W O R D S: Results One-hundred and four studies met the selection criteria (19 191 fetuses). In a high-risk population, umbilical artery Doppler predicted small-for-gestational age with a pooled LR+ of 3.76 (2.96, 4.76) and pooled LR− of 0.52 (0.45, 0.61), and compromise of fetal/neonatal wellbeing with a pooled LR+ of 3.41 (2.68, 0.62). In this group it was also possible to predict, with accuracy, intrauterine death (pooled LR+ = 4.37 (0.88, 21.8); 0.91)) and acidosis (pooled LR+ = 2.75 (1.48, 5.11);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Maternal history of a prior SGA newborn with normal fetal growth in the current pregnancy is not an indication for antenatal fetal heart rate testing, biophysical profile testing, or umbilical artery Doppler velocimetry (103). Any patient with a prior birth of an SGA newborn should have her medical and obstetric histories reviewed to help identify any additional risk factors, particularly modifiable risk factors.…”
Section: How Should Women With a Prior Birth Of A Small For Gestationmentioning
confidence: 99%
“…Maternal history of a prior SGA newborn with normal fetal growth in the current pregnancy is not an indication for antenatal fetal heart rate testing, biophysical profile testing, or umbilical artery Doppler velocimetry (103). Any patient with a prior birth of an SGA newborn should have her medical and obstetric histories reviewed to help identify any additional risk factors, particularly modifiable risk factors.…”
Section: How Should Women With a Prior Birth Of A Small For Gestationmentioning
confidence: 99%
“…A recent meta-analysis concluded that umbilical artery velocity patterns were moderately useful in predicting fetal distress. 11 Doppler ultrasound measurements at the middle cerebral artery (MCA) have showed brain sparing physiology by detecting reductions in the pulsatility of blood flow in cases of fetal growth restriction 12 and in fetuses with congenital heart disease. 13 Doppler ultrasound measures the velocity of the flowing blood but does not provide direct information on fetal oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…Given these recommendations (pertinent only in the setting of a SGA fetus), current practice in some quarters of incorporating the CPR (or even MCA‐PI) when the EFW is >10 th centile (unless there is also evidence of reduced AC or EFW growth velocity) into clinical management should be discouraged. There is precedence for our view: in the USA, routine UA and MCA Doppler measurement in the setting of appropriate fetal growth often does not attract any insurance reimbursement as these parameters have been shown to be of benefit only in high‐risk populations and of limited prognostic value for fetal or neonatal wellbeing.…”
mentioning
confidence: 99%